INDONESIAN BANKING STRATEGY IN IMPROVING CREDIT DISTRIBUTION - Aviliani, Aviliani (Dinasti International Journal of Digital Business Management, 2022)
This research is performed in order to test the influence of the variable Third-party Funds, Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operational Efficiency Ratio toward Credit Distribution at Banking in Indonesia. The data used in this research was obtained from the annual financial report data period 2015-2019. The sample used in this research is 10 General Bank of 43 General Bank at Indonesian Stock Exchange. The results show that the Third-party Funds, CAR, NPL, LDR, and Operational Efficiency Ratio against credit distribution. The results show that the partial of five variables that influence are variable Third-party Funds significantly, Capital Adequacy Ratio significantly, and Operational Efficiency Ratio significantly, While variable Non Performing Loan did not influence significantly, and Loan to Deposit Ratio did not influence significantly to credit distribution.